Quantitative assessment of the impacts of climate and human activities on streamflow of the Lancang-Mekong river over the recent decades - Li, Renzhi; Huang, He Qing; Wang, Zhonggen; Zhao, Ruxin (Frontiers in Earth Science, 2023)
The impacts of climate and human activities exerted on streamflow over the recent decades in the Lancang-Mekong River Basin (LMRB) have been examined in separate forms and this study performed an integrated quantitative evaluation. Using the meteorological and hydrological data measured in LMRB during 1961 to 2015, we analyzed the varying trend and abrupt change characteristics of streamflow along the river course, and constructed a SWAT hydrological model to quantitatively evaluate the contributions of climate and human activities by taking into account their spatial heterogeneity. At the yearly timescale, the results show that for significant complex changes in streamflow along the Lancang-Mekong River, the ratios of the contributions of the impacts of human activity (η_h) before 2000 to those after 2000 are under 15.2%, 17.5% and 32.4% respectively in the source area above Jiuzou (China), the upper area between Jouzhou and Yunjinghong (China), and the middle area between Jiuzhou and Vientiane (Laos). In the lower area between Vientiane and Stung Treng (Cambodia), η_h was only 22.6% before 2000 and yet dramatically increased to 59.1% after 2000. While the same situation happened at the seasonal time scale, η_h has relatively larger values during dry seasons than in wet seasons. In contrast to the gradually increased impacts of human activities, the impacts of climate on streamflow gradually decreased from the upper to the lower areas. Furthermore, the impacts of the changes in land use types account for about 1/3 in the Lancang River Basin and yet reaches more than 1/2 in the Mekong River Basin.